Developing improved methodologies for the quantification of microplastics in wastewater treatment plant effluent and sludge - Stanton, Thomas (2016)
The wastewater treatment process has long been recognised as a potentially significant source of microplastic pollution in freshwater environments. Though a handful of studies have demonstrated this emission across Europe and North America, a lack of consistency in the methodological approaches taken hinders the comparison of these studies. To address this limitation, an alternative methodological approach was developed for the sampling of wastewater treatment plant (WWTP) effluent which eliminates sample contamination by synthetic fibre deposition during the processing of aquatic samples. Alongside this, a methodology was developed for the processing of samples of sewage sludge, and the soil to which it is applied, that effectively separates microplastics from the organic and organo-mineral compositions of sludge and soil samples respectively, achieving a mean extraction efficiency of 81.9 %. The effluent of a large WWTP in the East Midlands was then processed, from which this study was able to determine that synthetic fibres were released in greater quantities than microplastic fragments over the short period during which samples were collected. Recommendations for further methodological refinement are made and the need for authoritative methodological standardisation is recognised.